Rational choice theories: the case of Frente Amplio and the pulp mills - Agustín Portilla (Revista Colección, 2017)
This article focuses on Broad Front's electoral campaign in 2004, seeking to determine to what extent the electoral strategies adopted impacted on the way in which this political force took position, along the period, about the possible installation of two pulp mills near Fray Bentos. In that sense, it is stated that two complementary strategies were implemented. The first one entailed a process of political moderation with the purpose of expanding its traditional leftist support toward the center. The second one implied vagueness about certain issues in order not to activate various internal contradictions, for example the cellulosic question. The absence of an official position enabled the various constituent elements of the coalition to expedite freely on the matter. While the majority were favorable to the ventures, opponents argued in a much more active way, giving rise to later misinterpretations about the position assumed by the Broad Front throughout the study period.